Does microstructure matter for statistical nanoindentation techniques? - Constantinides, Georgios; Ulm, Franz Josef; Vandamme, Matthieu; Jennings, Hamlin M.; Vanzo, James; Bentivegna, Michelle; Krakowiak, Konrad J.; Bobko, Christopher P.; Vliet, Krystyn J Van (My University, 2010)
In their paper, Trtik et al. (2009) identify spurious peaks in the application of statistical nanoindentation technique as a critical obstacle for mechanical phase identification. In this discussion, we show that Trtik et al.'s finding is a consequence of an unrealistic virtual 3-D checkerboard microstructure considered by the authors. These peaks are not a general feature of indentation on multiphase materials, nor can the presence of such peaks be attributed to an intrinsic shortcoming of the grid-indentation technique. We also show that the authors' assertion of the absence of homogeneous material regions extending beyond 3 μm in cementitious materials is groundless.
Keywords: Microstructure; Statistical methods; Cement composites